2021
DOI: 10.1136/bmjopen-2021-051549
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular morbidity and mortality in patients with type 2 diabetes using novel antidiabetic medicines as add-on therapy: an observational real-world study

Abstract: ObjectiveTo evaluate the effect of sodium-glucose co-transporter 2 inhibitors (SGLT2i) and glucagon-like peptide-1 receptor agonists (GLP-1RA), compared with dipeptidyl peptidase-4 inhibitors (DPP-4i) as add-on therapy on cardiovascular (CV) morbidity and mortality in patients with type 2 diabetes (T2D).Design and settingA nationwide cohort study using three linked healthcare databases from Slovenia (outpatient prescription claims data, hospitalisation claims data and death registry data).ParticipantsPatients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Overall, GLP-1RA significantly reduced the composite cardiovascular outcome by 18% (HR 0.82, 95% CI 0.73-0.91, I 2 = 4%) and MACE by 30% (HR 0.70, 95% CI 0.58-0.84, I 2 = 72%) (Figure 2A,B). All-cause mortality was found to be also reduced to an even greater extent with GLP-1RA use in all considered studies regardless of the comparator [21][22][23][24][25][26] (HR 0.61, 95% CI 0.52-0.73, I 2 = 88%) (Figure 2C). Only some studies investigated cardiovascular death, suggesting a significant benefit on this particular outcome (HR 0.66, 95% CI 0.49-0.88, I 2 = 63%) (Figure 2G).…”
Section: Cardiovascular Outcomes In Real-world Studies Comparing Pati...mentioning
confidence: 85%
See 2 more Smart Citations
“…Overall, GLP-1RA significantly reduced the composite cardiovascular outcome by 18% (HR 0.82, 95% CI 0.73-0.91, I 2 = 4%) and MACE by 30% (HR 0.70, 95% CI 0.58-0.84, I 2 = 72%) (Figure 2A,B). All-cause mortality was found to be also reduced to an even greater extent with GLP-1RA use in all considered studies regardless of the comparator [21][22][23][24][25][26] (HR 0.61, 95% CI 0.52-0.73, I 2 = 88%) (Figure 2C). Only some studies investigated cardiovascular death, suggesting a significant benefit on this particular outcome (HR 0.66, 95% CI 0.49-0.88, I 2 = 63%) (Figure 2G).…”
Section: Cardiovascular Outcomes In Real-world Studies Comparing Pati...mentioning
confidence: 85%
“…Pineda et al found that GLP-1RA initiation significantly reduced the risk of the composite cardiovascular outcome by 29% [17], while Yang et al and O'Brien et al demonstrated a 27% [18] and 22% [19] risk reduction vs. DPP-4i users, respectively; in contrast, Patorno et al observed no significant difference between treatment groups [20]. GLP-1RA produced a significant reduction in MACE risk, ranging from 10 to 45% when compared to DPP-4i [18,[21][22][23][24]. We carried out a meta-analysis of the cardiovascular effects of GLP-1RA vs. other glucose-lowering drugs as observed in real-world studies.…”
Section: Cardiovascular Outcomes In Real-world Studies Comparing Pati...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the beneficial effects of SGLT2i on cardiovascular and renal outcomes also should be considered when prescribing SGLT2i. The beneficial effect of SGLT2i on cardiovascular morbidity and mortality was also shown in another study that evaluated cardiovascular outcomes of Slovenian patients with type 2 diabetes [ 15 ].…”
Section: Resultsmentioning
confidence: 71%
“…We used three National Institute of Public Health (NIJZ) databases from Slovenia (Outpatient Prescription Medicines Database, National Hospital Health Care Statistics Database, and Causes of Death Registry) for the period 2009 to 2019. The databases, respectively, contain information on outpatient prescription claims, hospitalisation claims, and patient death for the entire Slovenian population (a detailed description of the databases is provided elsewhere [ 15 ]). The study protocol was registered at the European Network of Centres for Pharmacoepidemiology and Pharmacovigilance (registration number: EUPAS32558).…”
Section: Methodsmentioning
confidence: 99%